Papua New Guinea survey report: Rural household survey on food systems - Schmidt, Emily; Gilbert, Rachel; Holtemeyer, Brian; Rosenbach, Gracie; Benson, Todd (International Food Policy Research Institute, 2019)
Between May and July 2018, the International Food Policy Research Institute (IFPRI) implemented a household-level survey in four areas of PNG: the Autonomous Region of Bougainville (South Bougainville near Buin), Madang (Middle Ramu near Kwanga Station), East Sepik (near Maprik) and West Sepik (near Nuku). The survey investigated the food systems of rural households and how they assure sufficient food to meet the nutritional needs of their household members. The household questionnaire for the survey focused on agricultural production systems and health outcomes and included modules on: production; consumption and expenditure; labor activities (farm and non-farm); nutritional status; and the experience of the survey households with recent agricultural production or other shocks that impacted their livelihoods. This report provides descriptive results from the survey and discusses key indicators and actions to improve agricultural systems and nutrition in PNG.